PENERAPAN KONSEP TRIAS POLITICA PADA MORFOLOGI DAN TIPOLOGI KOTA WASHINGTON, D. C. DAN CANBERRA - Herliana, Emmelia Tricia (Universitas Atma Jaya Yogyakarta, 2013)
Abstract: City planning is intended to create better living environment for its residents. A city is â€˜a living laboratoryâ€™ that can be learned by people from different nations and cultures or even by the next generation, particularly by the next city planners. The morphology and typology of Washington, D.C. and Canberra, as federal capital cities of the central government, are determined by the early phase of planning, in which the planners interpreted the concept of the power system that each government has and implemented it to the structure of city. This study has an aim to oversee and compare the implementation of governmental power system in USA and Australia to the urban structure of their civic center. Both of them are democratic nations, which apply the concept of â€œTrias Politicaâ€, and this concept is implemented within the morphological and typological structure of the capital cities. The method to discuss this topic is, firstly, by describe the history of city planning and design of the two cities. Secondly, the difference of the implementation of â€œTrias Politicaâ€ concept to the basic concept of planning and to the elements of morphology and typology of each city is analyzed. Thirdly, the conclusion of previous discussion is configured. The result of this study is a comparison of the implementation of the concept in differentiating power of legislative, executive, and judicative to the city planning which applied Baroque and Beaux-Arts ideas on Washington, D.C. and Canberra.Keywords: Morphology, typology, capital city, civic center, â€œTrias Politicaâ€Abstrak: Perencanaan kota bertujuan untuk menciptakan lingkungan bermukim yang lebih baik bagi penduduk kota. Kota yang direncanakan dengan baik diharapkan akan dapat berfungsi dengan baik pula. Morfologi dan tipologi Kota Washington, D.C. dan Canberra, yang berfungsi sebagai ibukota pusat pemerintahan, sangat ditentukan oleh bagaimana para perencana dan perancang kota sejak awal menterjemahkan sistem kekuasaan yang dianut oleh pemerintah negara tersebut ke dalam struktur kota. Studi ini bertujuan untuk melihat dan membandingkan bagaimana konsep yang dianut oleh kedua negara, yaitu United State of America dan Australia, di dalam menjalankan kehidupan bernegara yang menerapkan paham demokrasi, yaitu konsep â€œTrias Politicaâ€, diterapkan pada struktur morfologi dan tipologi ibukota kedua negara. Metoda pembahasan yang digunakan adalah dengan menguraikan sejarah perencanaan dan perancangan kota Washington, D. C. dan Canberra, menganalisis perbedaan penerapan konsep â€œTrias Politicaâ€ pada konsep dasar perancangan dan unsur-unsur morfologi dan tipologi masing-masing kota, serta menarik kesimpulan dari pembahasan tersebut. Hasil dari studi ini berupa perbandingan penerapan konsep pembagian kekuasaan pada paham demokrasi melalui perancangan kota yang menerapkan gagasan Baroque dan Beaux-Arts pada kota Washington, D.C. dan Canberra. Studi ini dapat dijadikan sebagai bahan pembelajaran dan dapat diambil maknanya apabila para perencana dan perancang kota dihadapkan pada permasalahan di dalam merencana dan merancang kota atau mengevaluasi perencanaan dan perancangan yang sudah ada.Kata kunci: Morfologi, tipologi, ibukota, pusat pemerintahan, â€œTrias Politicaâ€